UTILIZING “TIME PIE” TO TEACH SPEAKING OF DAILY ACTIVITIES TO THE EIGHTH GRADERS OF SMP NEGERI 46 SURABAYA (RETAIN, 2015)
Abstract Pusparini, AulyaHadi. 2015. Utilizing “Time Pie” to Teach Speaking of Daily Activities to the Eighth Graders of SMP Negeri 46 Surabaya. Language and Literature Department, Surabaya State University. Advisor: EstiKurniasih, S.Pd.,M.Pd. Keywords: Time Pie, speaking, daily activities, eighth graders, students’ performance. This research was done to describe how the English teacher implemented “Time Pie” in teaching speaking of Daily Activities to the eighth graders of SMPN 46 Surabaya and to describe the students’ performances toward it. The design of this research is qualitative research. To obtain those kinds of data, the researcher used field notes and video recordings as the research instruments. The result of this study shows that the implementation of “Time Pie” done by the English teacher of SMP Negeri 46 Surabaya ran well. However, he skipped one stage of five stages that the English teacher must follow to teach English speaking to the students. The skipped stage was Responsive stage. It was still fine to skip this stage, because he still did the activity in the Interactive stage. It is similar with responsive stage, but the length and the complexity of this stage is quite harder. Besides, the English teacher of SMP Negeri 46 Surabaya applied “Time Pie” introduced by Rivera one by one. It seemed that the teacher missed one thing, which is he must ask the students to draw a big circle in the middle of a piece of paper and divide it according to the percentage of each activity. It was still fine because the students were still able to read their “Time Pie” and to find out which activity that they spent often and occasionally. While for the students’ speaking performance, the students of SMP Negeri 46 Surabaya are successful speakers. They chose the right vocabularies to transfer their ideas. Through “Time Pie”, the students could practice their oral skill to talk about their Daily Activities. From the students’ speaking performance, it is known that the students were able to use the correct grammatical features, the correct choice of vocabularies and they are fluent in talking about their Daily Activities. Based on the students’ speaking fluency, the students of SMP Negeri 46 Surabaya in class VIII˗F can be categorized into three categories. Those are Very Good, Good and Fair category.